2009
DOI: 10.2174/157341309787314557
|View full text |Cite
|
Sign up to set email alerts
|

Boron Nitride Nanotubes: A Novel Vector for Targeted Magnetic Drug Delivery

Abstract: Whereas several biomedical applications of carbon nanotubes have been proposed, the use of boron nitride nanotubes (BNNTs) in this field has been largely unexplored despite their unique and potentially useful properties. Our group has recently initiated an experimental program aimed at the exploration of the interactions between BNNTs and living cells. In the present paper, we report on the magnetic properties of BNNTs containing Fe catalysts which confirm the feasibility for their use as nanovectors for targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 26 publications
0
51
0
Order By: Relevance
“…Thus the BNNT usage is preferred, as far as nanotubebased device applications are expected at high temperatures and in chemically active and/or hazardous environments. 9 Although their use as vectors for drug delivery 10 or MRI contrast agents is foreseen, 11 the application of BNNTs in biomedicine remains largely unexplored. In particular, the interaction of BNNTs with living cells has not been addressed yet extensively.…”
Section: à5mentioning
confidence: 99%
“…Thus the BNNT usage is preferred, as far as nanotubebased device applications are expected at high temperatures and in chemically active and/or hazardous environments. 9 Although their use as vectors for drug delivery 10 or MRI contrast agents is foreseen, 11 the application of BNNTs in biomedicine remains largely unexplored. In particular, the interaction of BNNTs with living cells has not been addressed yet extensively.…”
Section: à5mentioning
confidence: 99%
“…These studies greatly enhanced our understanding on the properties of BNNTs. They show that BNNTs could be used in many potential applications especially nano-biomedical application222324252627.…”
mentioning
confidence: 99%
“…The cell compatibility of BNNTs was first studied by Ciofani et al [8]. Research results show that poly ethylene imine modified BNNTs does not produce great influence [9] on neuroblastoma survival, metabolism and cell regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorophenol (CPs) pollutants is the formation of dioxin pops precursor, has strong teratogenic, carcinogenic and mutagenic. As a new material to explore the removal these pollutants, using density functional theory (8,0) to research the adsorption behavior and mechanism of action of single wall boron nitride nanotubes (BNNT) and Co doped (8,0) single-walled boron nitride nanotube (Co-BNNT) to 2-(2-CP), 2,4,6-three chlorophenols (TCP), chlorophenols pentachlorophenol (PCP) . The results showed that compared with BNNT, Co-BNNT near the Fermi level is a hybrid state, the band gap decreases.…”
Section: Introductionmentioning
confidence: 99%